Financial Literacy for Young Entrepreneurs in Calculating Cost of Production and Break Event Point: Financial Literasi Bagi Pengusaha Muda dalam Menghitung Harga Pokok Produksi dan Break Event Point - Sari, Vita Fitria; Pebriyani, Dewi; Delfiani, Silvi (Yayasan Ahmar Cendekia Indonesia, 2023)
Higher education in Indonesia is required to prepare graduates not only academically but also have an entrepreneurial spirit to compete in the current era of globalization. Considering the current high unemployment rate, it is hoped that college graduates will not only look for work (job seekers) but also create jobs (job creators). This community service focuses on young entrepreneurs who joined HIPMI PT at Universitas Negeri Padang to solve their problems such as the lack of financial literacy mentors and members' lack of desire to learn effective and efficient business financial management. Therefore, the team provide training to increase financial literacy through workshop and assistance in calculating the cost of production and break event point analysis for young entrepreneurs. This community services had succeeded in increasing the financial literacy of young entrepreneurs, and it is hoped that can be applied to running the business they are involved in. Abstrak Perguruan tinggi di Indonesia dituntut untuk mempersiapkan lulusannya tidak hanya secara akademis namun juga memiliki jiwa kewirausahaan untuk bersaing di era globalisasi saat ini. Mengingat tingginya angka pengangguran saat ini, lulusan perguruan tinggi diharapkan tidak hanya mencari pekerjaan (job seeker) tetapi juga menciptakan lapangan kerja (job creator). Pengabdian masyarakat ini fokus pada para wirausaha muda yang tergabung dalam HIPMI PT di Universitas Negeri Padang untuk menyelesaikan permasalahan mereka seperti kurangnya pendampingan literasi keuangan dan kurangnya keinginan anggota untuk mempelajari pengelolaan keuangan bisnis yang efektif dan efisien. Oleh karena itu, tim memberikan pelatihan untuk meningkatkan literasi keuangan melalui workshop dan pendampingan penghitungan harga pokok produksi dan analisis break event point bagi wirausaha muda. Pengabdian kepada masyarakat ini berhasil meningkatkan literasi keuangan para wirausaha muda, dan diharapkan dapat diterapkan dalam menjalankan usaha yang digeluti.